PERAN PEMERINTAH KOTA DEPOK DALAM PENANGANAN MANTAN ANGGOTA GAFATAR - M. Agus Noorbani (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2018)
One of the the policy directions of the government in order to strengthen harmonious life of religious communities is to protect religious minority groups and religion-based trauma healing. This qualitative descriptive-designed research is an evaluative study to the local unit force of Depok City which has authority to deal with ex-Gavatar members and other citizens who were recorded as ex-Gavatar members. The research discovers that in dealing with ex-Gavatar members, the government of Depok City is still limited in picking up, data collecting, sheltering, psychological consulting, and returning them home. In addition, the post-returning action is limited in the observation and supervision of state-national insight. There has not been a policy to provide personal training and mentoring to the ex-Gavatar members. Some of their civil rights are still ignored. This includes services of population administration, education, and return on their assets in Kalimantan. The obstacle factor in dealing with ex-Gavatar members is mainly in the inflexible budget when facing social dynamics, especially when dealing with victims of social conflicts.